Letter from T. J. Glover to Arnold O. Beckman - Glover, T. J. (1935)
The letter regards Arthur Noyes's test results and serum supplied for his treatment.
Keywords: Blood--Analysis; Noyes, Arthur A. (Arthur Amos), 1866-1936; Cancer--Treatment